Role of Centella asiatica in Alzheimer’s Disease: A Comprehensive Review - Sinchana S Bhat (International Journal of Brain Sciences, 2024)
Alzheimer's disease (AD) is a progressive neurological illness that causes cognitive decline and memory loss and affects millions of people worldwide. As synthetic medications often prove ineffective or cause severe side effects, natural remedies are gaining attention. This review explores the potential of Centella asiatica, a herb traditionally used in oriental medicine, in the treatment of Alzheimer's disease. Triterpenoids, asiaticoside, and madecassoside are among the bioactive substances found in Centella asiatica that contribute to its therapeutic qualities. Studies suggest that Centella asiatica may enhance cognitive function through multiple mechanisms, such as inhibiting acetylcholinesterase activity, reducing phospholipase A2 activity, protecting against β-amyloid formation, and modulating oxidative stress responses. The plant's effects on neuronal morphology, learning performance, and memory retention have been demonstrated in animal models. Centella asiatica extract mitigates oxidative stress generated by Aβ plaques in the hippocampus and cortex. While these results are exciting, more research is needed to fully understand the mechanisms of action of the herb and assess its usefulness in human clinical trials. This review highlights the potential of Centella asiatica as a promising natural intervention for Alzheimer's disease and emphasizes the need for continued investigation into its therapeutic applications.
Keywords: Alzheimer's Disease; Centella asiatica; antioxidant; cognitive enhancement; neuroprotection